PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS SCIENTIFIC PADA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII SMP - -, Pajri - (Pendidikan Biologi, 2014)
Teaching material is a set of teaching materials which is arranged in systematic and showing the competencies completely that will students master in teaching and learning activities. By teaching materials the students will be able to learn each competence systematically so that in cumulatively the students are able to master all competencies as a whole and integrated. The achievement of the quality of education, it need tools that can help the teaching and learning process. It is called students worksheets (LKS). LKS existing in the school is not equipped with a color image that cannot attract the attention of students. Dealing with that problem, it is developing instructional media in the form of worksheets material organization of life systems at VII class in SMPN. . This research is aimed to determine the validity and the practicalities of scientific-based worksheets. This research is the developments of the use of 4-D Models consisting of four stages, namely; define, design, develop and disseminate are not done. Test results based scientific validity LKS, validator indicates that the LKS which is valid criterion in 84.67% in terms of didactic variables, construction and technical. Test results based scientific practicalities worksheets by teachers indicate that LKS is very practical criteria is 91.98% and the practicalities of the students test results shows that the LKS Scientific extremely practical criteria is 90.00% in terms of the aspects of easily of use, benefits and efficiency. LKS based on material scientific organization of life resulting system is valid and very practical.